Robotic-assisted vs non-robotic traction techniques in endoscopic submucosal dissection for malignant gastrointestinal lesions - Zhao Meng; Zhanghua Huang; Bingli Deng; Liuming Ling; Yaowen Ning; Shoaib Mohammed Rafiq (Frontiers in Oncology, 2022)
Endoscopic submucosal dissection is an effective approach with higher en bloc resection and complete resection rate for superficial gastrointestinal (GI) lesions. However, endoscopic submucosal dissection is technically challenging and associated with several adverse events, such as bleeding or perforations. The single channel flexible endoscope’s intrinsic limitations in preserving visualization of the submucosal dissection plane as compared to laparoscopic surgery are the most common cause of complications during the endoscopic submucosal dissection technique. As a result, traction techniques were created as the endoscope’s second helping hand in order to improve the effectiveness of the endoscopic submucosal dissection method. Trainees can master endoscopic submucosal dissection methods more quickly by using traction techniques. The anatomical location of the lesion plays a major role in determining which traction technique should be employed. An appealing way of traction is robot-assisted endoscopic submucosal dissection, and various types of endoscopic robots that allow bimanual operation are currently being developed. The advent of robot-assisted endoscopic technology ushers in a new era of endoscopic submucosal dissection, and with it come its own unique challenges that remain to be elucidated. Future research and development efforts are needed to focus on pathways and curriculums for trainees to master the currently available traction techniques and provide avenues for the development of newer traction modalities. In this article, we discuss evolution, characteristics, technological improvements and clinical comparisons of both robotic and non-robotic endoscopic traction techniques used in endoscopic submucosal dissection.